Ohmic heating in food processing (CRC Press, 2014)
"This special volume is devoted to Ohmic heating of foods covering several aspects of its science and engineering, chemistry and physics, biochemistry and nutrition, quality and safety, development and technology, both basic and applied. The structure of this volume is uniquely different from other publications although covering most in a general sense to make them more interesting. The book tells readers how important the technology is and how to implement in practice. The book covers basic theory, principles, and applications of Ohmic heating technology and is divided into several sections with chapters addressing specific issues related to Ohmic heating. Each chapter provides a critical review of the state of knowledge of published research and combined with the personal experience of the authors. While addressing processing, the physical principles, chemical and microbiological basis of the process are dealt with. The impact of the technology on the quality and safety of food, novelty of the technology for food processing are also highlighted. The book is designed primarily to be a valuable tool to graduate students and researchers as a source of information extending the contents of classical books on food processing while some chapters serve as standalone reference material. Each chapter is designed to be a valuable tool to food scientists and food technology professionals in the industry, wanting to follow new developments in food processing. Section 1 covers the basics of Ohmic heating and is written by one of the world experts in the areas, Dr. Sudhir K. Sastry, from Ohio State University. Chapter 1 gives an historic overview of the developments in Ohmic heating along with a brief review of present status and future outlook"-- Provided by publisher.
Keywords: Food -- Preservation.; Food industry and trade -- Quality control.; Electric currents -- Heating effects.; Electric fields -- Industrial applications.; elektronické knihy; electronic books